CITOMEGALOVIRUS: DE LA INFECCIÓN NEONATAL A LAS INFECCIONES EN PACIENTES TRASPLANTADOS Y DE LA CITOMEGALIA A LA BIOLOGÍA MOLECULAR - Boza Cordero, Ricardo (2011)
Human cytomegalovirus (CMV) is a herpesgroup virus, subfamily betaherpesviridae type 5,with a worldwide distribution. It appears in hu-mans and some other animals, and it is speciesspecific. Human acute infection frequently occurs on early life stages in developing countriesand in these areas nearly 100% of the adult popu-lation has been in contact with the virus, asdemonstrated by the high seroprevalence ratesobserved; in contrast in developed countries theseroprevalence is lower. This difference mainlyrelates to the close contact between persons andbodily secretions from early ages. Acute infec-tions are usually asymptomatic; symptomaticforms are more frequent and severe in individuals with conditions associated with cellular immunity impairments, as in the transplacentaltransmission to the product due to immaturity ofthe immune system, or in cases of immuno-supression due to HIV infections, treatment withimmunosuppressive drugs or in patients withhematopoietic stem cells transplant or solid organ transplant. Severe infections observed onimmunocompetent patients are rare. Followingthe acute infection, the virus progresses to alatent phase, reactivating during pregnancy orimmunosupression conditions. Recent advancesin immunopathogenesis, new diagnostic methodsand better antiviral drugs have led to better management of these infections. The objectives ofthis review are to present a historical analysis ofthis infection in humans, its pathogenesis, epi-demiology, clinical manifestations, the evolutionof diagnostic methods and its treatment, with anemphasis on the experience acquired while managing this condition at the Infectious DiseasesDepartment of the San Juan de Dios Hospital(HSJD).